Religious Role in Moderating Muzakki’s Decision to Issue Zakat - Busnetty, Ida; Faisal, Yusuf (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2024)
Purpose: This study aims to test and analyze the influence of Maqashid Shariah, Altruism, Income, Education with Religiosity as a moderating variableDesign/methodology: The method used in this study is a quantitative method. The population in this study is individuals who pay zakat through Baznas. Accidental sampling technique. The sample in this study amounted to 423 respondents. The data collection method uses a survey method, namely the author distributes the questionnaire directly to the respondents. The data analysis technique in this study uses SEM PLS. Findings: The results of this study found that there was a positive and significant influence of maqashid shariah on the decision of muzakki to issue zakat. Likewise, there is a positive and significant influence of altruism on the decision of muzakki to issue zakat. For income, there is a positive influence of income on the decision of muzakki to issue zakat, and there is a positive and significant influence of education on the decision of muzakki to issue zakat. As for moderating, namely religiosity, it strengthens the influence of maqashid shariah on the decision of muzakki to issue zakat. Religiosity weakens the influence of altruism on the decision of muzakki to issue zakat. Religiosity weakens the influence of income on the decision of muzakki to issue zakat. And religiosity strengthens the influence of education on the decision of muzakki to issue zakat Practical implications: The implications of this policy are expected to overcome the realization of zakat which is not directly proportional to the targeted zakat potential. The implementation and management of zakat in Indonesia has been stipulated in the Law of the Republic of Indonesia Number 23 of 2011, the government is also expected to develop social welfare programs such as the distribution of zakat funds for education, health and social assistance empowerment programs for people in need so that the muzaki will see the positive impact of the zakat issued which is expected to increase the decision of the muzaki to pay zakatOrisinalitas: This research enriches previous research regarding muzakki's decision to issue zakat such as altruism, income, education with the addition of religion. This research connects variables that people rarely examine, namely the existence of sharia maqashid which is viewed from the 5 dimensions of Hifdz Al Aql (protecting reason) with 4 indicators, Hifz An Nasl (protecting offspring) with 4 indicators, Hifz Al Mal (protecting wealth) with 7 indicators , Hift Ad Din (guarding religion) with 4 indicators, and Hift Nafs (guarding the soul) with 5 indicators.